Penurunan Kandungan Fosfat dalam Air dengan Zeolit - Rusvirman Muchtar (Jurnal Zeolit Indonesia, 2005)
The research was carried out to exploit the use of zeolite for phosphate absorption in the water. The result shows absorption of phosphate into 35 mesh Zeolite from Bayah and 5 ml/minutes stream velocity is 78 to 82 % while that into 50 mesh zeolite from Sukabumi and 5 ml/minutes stream velocity is 80 to 87 %. The saturated zeolite can be regenerated by 0,5 N NaOH.